Partial hybridisation of electron-hole states in an InAs/GaSb double quantum well heterostructure. (30th August 2017) - Knox, C S; Morrison, C; Herling, F; Ritchie, D A; Newell, O; Myronov, M; Linfield, E H; Marrows, C H
Abstract: InAs/GaSb coupled quantum well heterostructures are important semiconductor systems with applications ranging from spintronics to photonics. Most recently, InAs/GaSb heterostructures have been identified as candidate two-dimensional topological insulators, predicted to exhibit helical edge conduction via fully spin-polarised carriers. We study an InAs/GaSb double quantum well heterostructure with an AlSb barrier to decouple partially the 2D electrons and holes, and find conduction consistent with a 2D hole gas, with an effective mass of 0.235 ± 0.005 m 0, existing simultaneously with hybridised carriers with an effective mass of 0.070 ± 0.005 m 0, where m 0 is the bare electron mass.